Perceptions of falls risk and falls prevention among people with osteoarthritis. Issue 10 (8th May 2022) - Tsindos, Tess; Ayton, Darshini; Soh, Sze-Ee; Ackerman, Ilana N.
Abstract: Purpose: To understand the perceptions of falls risk and falls prevention, and the perceived enablers and barriers to engaging in falls prevention strategies/activities among people with doctor-diagnosed hip and/or knee osteoarthritis. Methods: A qualitative study utilising semi-structured telephone interviews. Researchers independently analysed qualitative data using an inductive method guided by the COM-B framework. Interviews were analysed thematically using open, axial, and selective coding. Recruitment ceased at 20 interviews, once data saturation was evident. Results: Participants were 18 women and two men aged 52–84 years and half had fallen in the last 12 months. Main themes were the absence of recommendations to access activities after having a fall, inconsistencies between perceptions of the relationship between OA and falls, and individual beliefs of not being at risk of falling because of taking precautions. Knowledge about falls prevention programs was limited, the term "falls prevention" was considered stigmatising and only applicable to older frail people. Home modifications were perceived as broadcasting negativity; participants felt falls terminology should be changed from a negative to a positive focus. Conclusions: Falls were often seen as inevitable consequence of keeping active. Re-framing the language used to discuss falls is recommended to promote uptake of falls prevention activities. Implications for rehabilitation: Despite growing evidence that osteoarthritis (OA) is an independent risk factor for falls, people with OA do not perceive themselves to be at risk and falls prevention is for those who are "old and frail". Re-framing the language used to discuss falls and falls prevention to focus on positive messages may promote the uptake of falls prevention activities in this population. Improving the awareness of falls and falls risk among people with OA through effective health education is needed in order to foster the uptake of, and engagement with, falls prevention activities.